Combined Function of Brønsted and Lewis Acidity in the Zeolite‐Catalyzed Isomerization of Glucose to Fructose in Alcohols. Issue 19 (14th September 2016) - Saravanamurugan, Shunmugavel; Riisager, Anders; Taarning, Esben; Meier, Sebastian
Abstract: Glucose conversion via fructose to useful chemicals and fuels has attracted considerable attention. Isomerization of glucose to fructose can proceed along several different reaction pathways involving different sugar intermediates and isomeric forms. Presently, the roles of the substrate isomeric forms and of the catalyst properties remain incompletely understood. By using NMR spectroscopy, we elucidate the interplay of the catalyst active sites in converting monosaccharide forms to products, byproducts, and intermediates in alcohols. Abstract : Acid traps sweetener : The interplay of active sites in zeolites is complex. The zeolites function as bifunctional catalysts for Lewis‐acid‐catalyzed isomerization of glucose to fructose and for Brønsted‐acid‐catalyzed trapping of fructose as fructosides. This leads to kinetic product control and enables higher than equilibrium yields of fructose to be obtained after hydrolysis.